'Are you on the market?': a capture-recapture enumeration of men who sell sex to men in and around Mombasa, Kenya. - Geibel, S; van der Elst, E; King'ola, N; Luchters, S; Davies, A; Getambu, E; Peshu, N; Graham, S; McClelland, R; Sanders, E (2007)
BACKGROUND: Men who have sex with men (MSM) are highly vulnerable to HIV infection, but this population can be particularly difficult to reach in sub-Saharan Africa. We aimed to estimate the number of MSM who sell sex in and around Mombasa, Kenya, in order to plan HIV prevention research. METHODS: We identified 77 potential MSM contact locations, including public streets and parks, brothels, bars and nightclubs, in and around Mombasa and trained 37 MSM peer leader enumerators to extend a recruitment leaflet to MSM who were identified as 'on the market', that is, a man who admitted to selling sex to men. We captured men on two consecutive Saturdays, 1 week apart. A record was kept of when, where and by whom the invitation was extended and received, and of refusals. The total estimate of MSM who sell sex was derived from capture-recapture calculation. RESULTS: Capture 1 included 284 men (following removal of 15 duplicates); 89 men refused to participate. Capture 2 included 484 men (following removal of 35 duplicates); 75 men refused to participate. Of the 484 men in capture 2, 186 were recaptures from capture 1, resulting in a total estimate of 739 (95% confidence interval, 690-798) MSM who sell sex in the study area. CONCLUSIONS: We estimated that 739 MSM sell sex in and around Mombasa. Of these, 484 were contacted through trained peer enumerators in a single day. MSM who sell sex in and around Mombasa represent a sizeable population who urgently need to be targeted by HIV prevention strategies.